Grassroots Artmaking (Bloomsbury Publishing (UK), 2026)
Grassroots Artmaking is a pioneering, open-access historical survey that compiles diverse studies, artist interviews, case studies, and roundtable discussions to explore how UK-based art activism has moulded contemporary art over six decades. Addressing political turmoil in the UK since the 1960s, marked by racist immigration laws, far-right ascent, nuclear proliferation, gender oppression and Thatcher's governance, this timely book traces the evolution of grassroots artistic self-organization as a means of resistance. From artist-led initiatives like the Caribbean Artists Movement and the Blk Arts Group, to AIDS activist visual production and community photography initiatives, it showcases a vital strand of British art history beyond mainstream institutions and geographic centres. Contextualizing the importance of this work in relation to recent seismic events such as austerity, Brexit, Covid, Grenfell, and BLM, the book brings contemporary and historical realities into dialogue with a uniquely cross-media perspective, covering photography and film-making, as well as multiple forms of organizing and artistic practice; from curating, archiving, and administration, to studio management, poster production and institution building. Richly illustrated with archival material from a wide range of sources, Grassroots Artmaking provides a lively, visually enticing account of the formative connections between grassroots activism and art practice. It lays the groundwork for a new approach to teaching modern and contemporary British art histories and will serve as an indispensable tool for researchers and artists alike. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by UKRI.